Loan growth and bank profitability of commercial banks in indonesia - Erin Wijayanti; Mardiana Mardiana (AKUNTABEL, 2020)
This study examines how loan growth affects profitability of commercial banks in Indonesia during the period from 2014 to 2018. The loan growth shows that banks will increase credit risk, so that is very important to manage credit quality and capital in maintaining the risk of loss. Purposive sampling method was utilized and 96 samples constitute the final samples of this study. This study uses a variance-based analysis of Structural Equation Modeling (SEM) based on variance, namely Partial Least Square (PLS). The results showed that loan growth had a significant positive effect on bank profitability, indirect loan growth had a significant positive effect on bank profitability with credit quality as an intervening variable and indirect loan growth had a negative and not significant effect on bank profitability with bank capital as an intervening variable.